Wirkende Bilder (Lebenswelt. Aesthetics and philosophy of experience., 2011)
The belief in the plastic power of imagination and of imagine is a fundamental part of human Psychology’s History. A look to the ground of this belief could clarify the cohabitation of science and superstition at the beginning of the Modern Age. Although in modern treatise from the field of subjectivity and unreality, imagination does not always enjoys the benefit of science. The power of imagination, as a faculty or as magical Medium between thought and being, allows belief to consider what is imagined as fundamental part of the processes of universe.